Techno-Economic Assessment of a Chopped Feedstock Logistics Supply Chain for Corn Stover - Wendt, Lynn M.; Smith, William A.; Hartley, Damon S.; Wendt, Daniel S.; Ross, Jeffrey A.; Sexton, Danielle M.; Lukas, John C.; Nguyen, Quang A.; Murphy, J. Austin; Kenney, Kevin L. (Frontiers in Energy Research, 2018)
Storing corn stover in wet, anaerobic conditions is an active management approach to reduce the risk of significant aerobic degradation and catastrophic loss due to fire. An estimated 50% of the corn stover available in the U.S. is too wet at the time of harvest to be stored safely in baled formats and is compatible with wet, anaerobic storage through ensiling. A logistics system based on field-chopping and particle size reduction early in the supply chain removes the dependency on field-drying of corn stover prior to baling, allows for an expanded harvest window, results in diminished size reduction requirements at the biorefinery, and is compatible with ensiling as a storage approach. The unit operations were defined for this chopped logistics system, which included field chopping, bulk transportation to a biorefinery site, on-site preprocessing to meet biorefinery size and ash specifications, industrial-scale storage through ensiling, and delivery of corn stover at a rate of 2,000 tonnes per day for ~50% of the year. The chopped system was compared to the conventional bale system for 30% moisture (wet basis) corn stover, a likely delivered moisture content for baled corn stover harvested wet. Techno-economic analysis showed that the chopped logistics system is cost competitive, costing only 10% more than the baled logistics system, meanwhile reducing the energy consumption by 48% and greenhouse gas release by 60%. In summary, a chopped logistics system utilizing on-site preprocessing and storage at a biorefinery gate is an economically viable approach to provide a stable source of corn stover for use when dry bales are not available, meanwhile reducing the risk of loss in long-term storage.